Spontaneous symmetry breaking and first-order phase transitions of adsorbed fluids - Sartarelli, Salvador Andrés (2010)
A density functional formalism is applied to investigate the wetting behavior of Ne confined in slits composed of two parallel solid identical alkaline walls with increasing attractive strength leading to a variety of wetting situations. The study is performed over the complete range of temperature spanned from the triple point Tt up to the critical one Tc of Ne. Attention is paid to the slit's width. It was found that in the case of weaker substrates for temperatures below a certain critical T sb the density profiles corresponding to the lowest free energy are asymmetric, i.e. exhibit a spontaneous breaking of symmetry. For T > T sb the phenomenon of symmetry breaking disappears leading to a first-order phase transition.